Penerapan Role-Playing (Bermain Peran) untuk Mengatasi Anger Expression pada Anak Usia Sekolah Dasar - Safitri, Febila Dara; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Anger expression or angry expression is one of the emotions that covers a person at a time. Especially this happens to children who are very difficult to overcome. Expressions of anger in children often occur in class, for example, such as fighting with friends, bothering friends who are studying, grabbing other people's things, and so on. This can create unexpected expressions such as anger, annoyance, fear, disappointment, and so on. Therefore, an alternative is required to overcome anger expression one of which is role-playing. The theory used is that the negative impact of emotions is to interfere with motor skills and interfere with mental activities. The role-playing is a form of learning activity in which children are actively involved in playing certain roles. This study researchers used a qualitative approach and methods of research used literature studies. The answer to problem’s formulation, researchers employ data collection techniques of literature and meta-analysis to address the problem and discussion in chart and descriptive form. Based on library results done by researchers, it could be concluded that the expected child’s expression of anger could be the student could reflect on events that would trigger emotions, such as not disturbing their friends who are seriously studying, asking for permission when borrowing items, staying calm during learning take place. As well as the literature found that role-playing is one of the games that has a good influence on dealing with children's emotions. So that role playing is used as an alternative to overcome angry expressions.